2022
DOI: 10.51986/ijer-2022.vol4.04
|View full text |Cite
|
Sign up to set email alerts
|

Headteachers' Leadership Practices and Students’ Discipline in Government Aided Secondary Schools in Bushenyi-Ishaka Municipality, Uganda

Abstract: This study examined the relationship between headteachers' leadership practices and students' discipline in secondary schools in Bushenyi-Ishaka Municipality, Uganda. Particularly, the study tested the relationship between headteachers' collaborative culture practice and students' discipline, the relationship between headteachers' distributed leadership practice and students' discipline, and the relationship between the headteachers' interpersonal relationships leadership practice and students' discipline. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Work integrated learning is already popularised by sectors in Canada and Europe and this is in some cases at the level of government (Gatto et al ., 2021; Rangraz and Pareto, 2021). Mugizi (2019) found that there was a gap between organisational commitment and employee training and development in many educational institutions in Wakiso district of Uganda. A synergy between HEIs and employee organisation will ease the pursuance of further studies during mid-career development and hence strengthen HR capacity building.…”
Section: The Case Of Ugandamentioning
confidence: 99%
“…Work integrated learning is already popularised by sectors in Canada and Europe and this is in some cases at the level of government (Gatto et al ., 2021; Rangraz and Pareto, 2021). Mugizi (2019) found that there was a gap between organisational commitment and employee training and development in many educational institutions in Wakiso district of Uganda. A synergy between HEIs and employee organisation will ease the pursuance of further studies during mid-career development and hence strengthen HR capacity building.…”
Section: The Case Of Ugandamentioning
confidence: 99%
“…The effectiveness of any school must be measured by what contributions it has made to improve the learning of the school students. This may not be achieved when there is poor leadership (Mugizi et al, 2022). Thus, in any organisation, the most important figures are the leaders since they are responsible for directing them towards the achievement of set goals.…”
Section: Literature Review Theoretical Literature Reviewmentioning
confidence: 99%